2021
DOI: 10.35502/jcswb.176
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of visual testing efficacy in detecting cannabis usage

Abstract: Drug recognition and examination programs are widely used to detect drug impairment in motor vehicle operators. Visual tests are a key assessment in the detection of cannabis-related impairment. Participants were recruited via social media from the medical cannabis community in Southwestern Ontario, Canada. Twenty-two participants completed the full observational trial design. The majority (n = 13 or 59.1%) were male, with a mean age of 36 years (SD = 9.4; range: 24–59). Participants underwent the following pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It has been reported that visual testing is not diagnostic for cannabis impairment (Olla et al, 2021), and mixed sensitivities of FSTs in identifying cannabis intoxication via inhalation and oral exposure have been reported. Bosker, Theunissen, et al (2012) concluded that cannabis inhalation was related to the OLS test in heavy users, which was later supported by the work of Porath‐Waller and Beirness (2014), Hartman, Richman, et al (2016), Declues et al (2016), and Spindle et al (2021).…”
Section: Current Legislationmentioning
confidence: 99%
“…It has been reported that visual testing is not diagnostic for cannabis impairment (Olla et al, 2021), and mixed sensitivities of FSTs in identifying cannabis intoxication via inhalation and oral exposure have been reported. Bosker, Theunissen, et al (2012) concluded that cannabis inhalation was related to the OLS test in heavy users, which was later supported by the work of Porath‐Waller and Beirness (2014), Hartman, Richman, et al (2016), Declues et al (2016), and Spindle et al (2021).…”
Section: Current Legislationmentioning
confidence: 99%